Options for business rate reform - Kevin Denny; John Hall; Stephen Smith (Institute for Fiscal Studies (IFS), 1995)
The national non-domestic rate was introduced in 1990 to replace a system of locally varying business rates which had lasted for almost four centuries. Five years after the. 1990 reforms, this report evaluates the operation of the present system and discusses various options for reform.
Keywords: 330